2009
DOI: 10.1143/jjap.48.010203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultraviolet Photo-Field Effects between Hydrogenated Amorphous Silicon and Amorphous InGaZnO4 Thin-Film Transistors

Abstract: We discuss the ultraviolet (UV) photo-field effects in amorphous InGaZnO 4 thin-film transistors (a-IGZO TFTs) compared with those in hydrogenated amorphous silicon (a-Si:H) TFTs. It is shown that the UV illumination induces a much more significant threshold voltage (V t ) decrease and OFF-current increase for the a-IGZO TFTs than for the a-Si:H TFTs. The significant V t decrease is found to take several tens of min to return to the initial state after switching off the UV light. A qualitative model is introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 13 publications
2
103
0
Order By: Relevance
“…It has been pointed out that the threshold voltages of a-IGZO TFTs are shifted markedly by exposure to light, even at subgap energies [78,79]. For photonic devices, the strong photoresponse may be good news, and the photoexcited carriers in a-IGZO fi lms appear to have long lifetimes.…”
Section: Summary: Present and Future Issuesmentioning
confidence: 99%
“…It has been pointed out that the threshold voltages of a-IGZO TFTs are shifted markedly by exposure to light, even at subgap energies [78,79]. For photonic devices, the strong photoresponse may be good news, and the photoexcited carriers in a-IGZO fi lms appear to have long lifetimes.…”
Section: Summary: Present and Future Issuesmentioning
confidence: 99%
“…A donor can capture carrier electrons with large lattice relaxations, forming a DX (donor (D) deactivated (X)) center, 1-5 whereas an acceptor traps holes, forming an AX (acceptor (A) deactivated (X)) center. [5][6][7] However, in amorphous semiconductors, even though many charge-trapping phenomena that can modify electronic device characteristics 8 and be applied to nonvolatile memory devices 9 have been observed, the atomic and electronic structures of the charge-trapping defects lack clear understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Takechi et al reported that these traps are light-induced oxygen interstitials. 12 The trapped charges enhance the TFT conductance and remain for a long period of time leading to a persistent photoconductivity (PPC). G€ orrn et al 13 and Gosain et al…”
mentioning
confidence: 99%